Disruption of Rab9-dependent mitophagy contributes to menopause-induced sarcopenia - Uebo, Shota; Ikeda, Yoshiyuki; Uchikado, Yoshihiro; Sasaki, Yuichi; Akasaki, Yuichi; Kubozono, Takuro; Ohishi, Mitsuru (Experimental gerontology, 2025)
Aim Sarcopenia, a major cause of frailty in postmenopausal women, is linked to mitochondrial dysfunction, but the underlying mechanisms remain unclear. This study aimed to clarify whether mitophagy, a mitochondrial quality control mechanism, contributes to postmenopausal sarcopenia, to elucidate its underlying mechanism, and to assess whether it can be rescued. C57BL/6 mice (12-week-old females) underwent ovariectomy to establish a menopause mouse model, or sham surgery, and the therapeutic effects of nicotinamide mononucleotide (NMN) were assessed. Human skeletal muscle myoblasts (HSMMs) differentiated under postmenopausal conditions with or without 17β-estradiol (E2), and Rab9 expression was modulated using CRISPR activation. Ovariectomized mice exhibited decreased muscle mass and strength. E2 deficiency in HSMMs inhibited skeletal muscle cell differentiation, promoted senescence, impaired mitochondrial function, and reduced mitophagy. However, E2 deficiency did not modulate light chain 3 and autophagy-related 7 but reduced Rab9 expression and the colocalization of Rab9 with lysosomal-associated membrane protein 2, suggesting that E2 mediates mitophagy through Rab9-dependent alternative autophagy. Furthermore, overexpression of Rab9 in E2-deficient HSMMs enhanced mitophagy, improved mitochondrial function, suppressed cellular senescence, and promoted skeletal muscle cell differentiation. The administration of NMN to ovariectomized mice increased Rab9 expression and improved sarcopenia through increased mitophagy. This study demonstrates that estrogen deficiency impairs mitophagy originated from Rab9-dependent alternative autophagy, leading to mitochondrial dysfunction and sarcopenia, while enhancement of Rab9 restores mitochondrial quality control and muscle function. These results identify Rab9-dependent mitophagy as a potential therapeutic target for postmenopausal sarcopenia. [Display omitted] •Estrogen deficiency impairs Rab9-dependent alternative mitophagy in muscle.•Rab9 activation restores mitochondrial function and muscle differentiation.•Nicotinamide mononucleotide (NMN) administration enhances Rab9 expression.•NMN rescues estrogen deficiency-induced sarcopenia.•Rab9 is identified as a novel therapeutic target for postmenopausal muscle loss.